FIRM SIZE SEBAGAI PEMODERASI PENGARUH LIKUIDITAS, LEVERAGE, DAN OPERATING CAPACITY PADA FINANCIAL DISTRESS - Eka Kartika Kariani, Ni Putu; Budiasih, I G.A.N (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Financial distress is a stage of decline in the company's financial condition that occurs prior to the bankruptcy or liquidation. The aim of research to determine the effect of liquidity, leverage, and operating capacity in financial distress with firm size as moderating variables. The study population includes manufacturing companies listed in Indonesia Stock Exchange for the period 2012-2015 as many as 121 companies, and obtained a sample of 13 companies. The method used in this research is purposive sampling method. The hypothesis was tested using moderation regression analysis. The result of the analysis is liquidity and operating capacity has no effect in financial distress, leverage has negative in financial distress. The Effect liquidity and operating capacity in financial distress are not able to be moderated by the variable firm size, the effect of leverage in financial distress is able to be moderated by the variable firm size.
Keywords: Financial Distress, Liquidity, Leverage, Operating Capacity, Firm Size